FORMULATION OF PROSECUTION OF CORRUPTION CRIMINAL ACTS BASED ON JUSTICE VALUES - Lubis, Muhammad Kenan; Winjaya Laksana, Andri (UNISSULA Semarang, 2024)
The implementation of the authority of the public prosecutor's criminal prosecution in handling non-corruption cases tends to be low, does not have a clear benchmark and the range of punishment for corruption crimes in the Corruption Law is wide. So that there is potential for abuse of authority in handling corruption crimes. The purpose of this study is to determine the prosecution of perpetrators of corruption crimes; analyze the basis for the public prosecutor's considerations in determining the severity of criminal charges against defendants in corruption cases; analyze the formulation of prosecution of perpetrators of corruption crimes based on the value of Justice in the future. The approach method used in this study is the normative legal method. The results of this study are (1) The current regulation of corruption crimes in Indonesia has been regulated through Law Number 31 of 1999 in conjunction with Law Number 20 of 2001, which stipulates corruption as an extraordinary crime with a law enforcement approach involving various institutions such as the Prosecutor's Office, Police, and KPK. Although law enforcement efforts have been carried out through investigation, inquiry, and prosecution mechanisms, the effectiveness of this regulation still faces challenges such as disparity in sentences, high costs of handling small corruption cases, and weaknesses in proving state losses. (2) The basis for consideration by the Public Prosecutor in determining the severity of the criminal charges against defendants in corruption cases includes aspects of legal certainty, justice, and benefit, as regulated in the law, the Attorney General's Circular, and legal principles. These considerations include the extent of state losses, the impact of corruption on society and the environment, and the extent to which the defendant enriches himself or others. (3) Determining a firm minimum criminal threat is necessary to prevent disparities in punishment and provide a deterrent effect, while sentencing guidelines must be designed so that judges have a clear basis in considering factors for mitigating or aggravating punishment.